Resilience and Livelihood dynamics of shrimp farmers and fishers in the Mekong Delta, Vietnam - Tran, Thi Phung Ha (Wageningen University, 2012)
This book introduction theoretical review and research setting, livelihood capabilities an pathways of shrimp farmer in the Mekong Delta, impacts of changes in mangrove forest managemetn practices on forest access livelihood, fishery livelihood and non-compliance with fishery regulations...